CONCURRENT CONTACT SENSITIZATION TO METALS IN DENTAL EXPOSURES - Maya Lyapina; Maria Dencheva; Mariana Cekova; Mariela Deliverska; Angelina Kisselova-Yaneva (Peytchinski Publishing, 2018)
Purpose: Sensitization to metals is a significant problem for both dental patients treated with dental materials and for dental professionals in occupational exposures. The purpose of the present study was to evaluate the incidence of concurrent contact sensitization to relevant for dental practice metals among students of dental medicine, students from dental technician school, dental professionals and patients. Material and Methods: A total of 128 participants were included in the study. All of them were patch-tested with nickel, cobalt, copper, potassium dichromate, palladium, aluminium, gold and tin. The results were subject to statistical analysis (p < 0.05). Results: For the whole studied population, potassium dichromate exhibited concomitant reactivity most often; copper and tin also often manifested co-reactivity. For the groups, exposed in dental practice, potassium dichromate and tin were outlined as the most often co-reacting metal allergens, but statistical significance concerning the co-sensitization to copper and the other metals was established only for aluminium. An increased incidence and OR for concomitant sensitization to cobalt and nickel was established in the group of dental students; to copper and nickel - in the control group; to palladium and nickel - in the group of dental professionals, the group of students of dental medicine and in the control group; to potassium dichromate and cobalt - in the group of dental students; to copper and palladium - in the control group of dental patients; to potassium dichromate and copper - in the group of dental professionals; to copper and aluminum - in the groups of students from dental technician school and of dental professionals; to copper and gold - in the groups of dental professionals and in the group of dental patients; to potassium dichromate and aluminum - in the group of dental professionals; to potassium dichromate and gold - in the group of dental professionals, and to aluminium and tin - in the groups of dental professionals and in the group of dental patients. Conclusions: Our data indicate a high risk of concurrent contact sensitization to the studied relevant for dental practice metals. Since the role of occupational exposures can't be excluded, adequate preventive measures and information should be provided. General population also need to be well informed and the European Union regulations to be properly applied.